Neoclassical Compositional Resources in Mario Castelnuovo–Tedesco's Sonata for Guitar Omaggio a Boccherini - Galindo Bicerra, Julio Daniel (2019)
Sonata Omaggio a Boccherini is considered one of the major pieces of contemporary guitar repertoire. Even though this composition has been the subject of some studies in the academic field, little has been said about its relationship with the trends of musical Neoclassicism in the twentieth century. Through this article, Ruth Piquer–Sanclemente's aesthetic concept of Neoclassicism and Martha Hyde's theory of metamorphic anachronism are employed to determine the compositional resources of Neoclassicism present in the Sonata Omaggio a Boccherini. To contextualize this study, an approach to the emergence and establishment of French Neoclassicism is made, as well as the way in which a vindication of guitar appears in Spain and Europe during this process. The main part of the article offers a musical analysis of specific fragments that state the presence of Neoclassical principles, work that is particularly deepened when dealing with the third movement Minuet. Finally, this study unveils the Neoclassical compositional resources employed in the creative process of the Sonata. The recognition of these elements allows us to explore how Castelnuovo-Tedesco developed characteristic compositional resources of the musical aesthetics of his time.